Հայոց Մեծ եղեռնի պատմագրությունը և մատենագիտությունը հետխորհրդային ժամանակաշրջանում - Մհեր Կարապետյան (ՀՀ ԳԱՍ Հայոց ցեղասպանության թանգարան-ինստիտուտ)
В области изучения историографии и библиографии Геноцида армян в постсоветский период проделана определенная работа: представлена и оценена коллективная работа «Новая история Армении в трудах современных зарубежных авторов» (Ереван, І993), изданная Институтом востоковедения НАН РА. In the field of study of a historiography and the bibliography of Genocide of Armenians in the post-Soviet period certain work has been made: collective work "The Modern history of Armenia in works of modern foreign authors" is presented and analyzed (Yerevan, 1993), issued by the Institute of Oriental Studies of National Academy of sciences.
Keywords: Պատմագրություն; Հայոց ցեղասպանություն (1915)